2021
DOI: 10.1016/j.celrep.2021.109094
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modulation of spleen germinal center reactions by gut bacteria during Plasmodium infection

Abstract: Highlights d Human gut bacteria composition correlates with severity of malaria d Gut bacteria dynamically modulate spleen GC reactions to systemic infection d Modulating gut bacteria can halt escalating parasitemia d Antibiotic-induced changes in gut bacteria can boost anti-Plasmodium host immunity

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(58 citation statements)
references
References 61 publications
4
54
0
Order By: Relevance
“…Here, we observed that baseline GI microbiota composition in humans was strongly associated with the potential for severe P. falciparum infection. Our findings are in agreement with observational studies using incident detection in human children in malaria endemic areas 19,20 and previous murine studies 2123 , both of which have suggested a link between GI microbiome composition and risk for severe malaria infection. Importantly, our work extends these observations to adult humans and highlights Bifidobacterium as a defining microbial feature in limiting risk for severe P. falciparum parasitemia.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Here, we observed that baseline GI microbiota composition in humans was strongly associated with the potential for severe P. falciparum infection. Our findings are in agreement with observational studies using incident detection in human children in malaria endemic areas 19,20 and previous murine studies 2123 , both of which have suggested a link between GI microbiome composition and risk for severe malaria infection. Importantly, our work extends these observations to adult humans and highlights Bifidobacterium as a defining microbial feature in limiting risk for severe P. falciparum parasitemia.…”
Section: Discussionsupporting
confidence: 93%
“…Downstream analyses indicated that key GI microbes, including Bifidobacterium longum, Bifidobacterium adolescentis , and Akkermansia muciniphila were detected less frequently and at lower abundances in participants that were more likely to develop severe parasitemia. Our findings extend previous observations made in the murine model 21-23 , as well as observational studies using incident detection in human children living in malaria endemic areas 19,20 , both of which suggested a link between GI microbiome composition and the risk of developing severe malaria infection. Importantly, our work extends these observations to adult humans and highlights Bifidobacterium as a defining microbial feature in determining risk for severe P. falciparum parasitemia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Studies in humans and mice have shown that gut microbiota is associated with the level of malarial disease in those living in malaria-endemic areas [68][69][70]. This has also been shown in mice [9,71], specifically with respect to modulating germinal center reactions [71], even within the spleen [72]. This is relevant in the selection of mouse vendor given clear evidence that the severity of erythrocytic Plasmodium infection in genetically similar mice obtained from different vendors was significantly altered in response owing to the differences in gut microbiome [9].…”
Section: Modelling the Influence Of Environmental Factors On Immune R...mentioning
confidence: 81%
“…This is true of malaria, where the gut microbiota influences disease severity caused by, and the immune response to, the parasite (e.g. [93][94][95]). A further particularly relevant example concerns trypanosome infections in the tsetse fly, where tsetse endosymbionts can have significant impact on the vectorial capacity of the arthropod [96].…”
Section: Evolutionary Implications and Areas That Need Developmentmentioning
confidence: 99%